Chronic Kidney Disease: A Case Series (Part 2) (Advancements in Homeopathic Research, 2023)
In their maiden publication (4) Gupta et. al. demonstrated that majority of patients of chronic  renal failure can be improved or at least prevented  from further deterioration by homoeopathic treatment  along with change in life style, strict diet and regimen  along with supportive medicines for controlling  diabetes and hypertension. Recently Gupta et.  al. published a series of 3 cases on successful  management of CRF(11) and proposed to publish  further series of best responding cases to update the  physicians about successful treatment of renal failure  by homoeopathic remedies, thereby avoiding dialysis  and renal transplant. This second case series is on  management of CRF by Natrum muriaticum selected  on the basis of individualization. The first case in this  series is a well-diagnosed, non-dialysed case of CKD  of a 56-year old hypertensive male with more than 4  years of follow-up. The second case is of a 40-year  old female with primary sterility with follow up of  3 years. The third case is of a 53-year old male with  hypertensive nephropathy with 3 year follow up. In  all the 3 cases, repeated renal function test and eGFR,  calculated by equation from the ‘Modification of Diet  in Renal Disease’ (MDRD) equation (5) considering  the age and creatinine, is considered the main  parameter to assess the functional status of kidney  and response to homoeopathic treatment.
Keywords: aemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment